On approaches to the functional restoration of salivary glands damaged by radiation therapy for head and neck cancer, with a review of related aspects of salivary gland morphology and development - Redman, RS (Biotechnic & histochemistry, 2008)
Radiation therapy for cancer of the head and neck can devastate the salivary glands and partially devitalize the mandible and maxilla. As a result, saliva production is drastically reduced and its quality adversely altered. Without diligent home and professional care, the teeth are subject to rapid destruction by caries, necessitating extractions with attendant high risk of necrosis of the supporting bone. Innovative techniques in delivery of radiation therapy and administration of drugs that selectively protect normal tissues can reduce significantly the radiation effects on salivary glands. Nonetheless, many patients still suffer severe oral dryness. I review here the functional morphology and development of salivary glands as these relate to approaches to preventing and restoring radiation-induced loss of salivary function. The acinar cells are responsible for most of the fluid and organic material in saliva, while the larger ducts influence the inorganic content. A central theme of this review is the extent to which the several types of epithelial cells in salivary glands may be pluripotential and the circumstances that may influence their ability to replace cells that have been lost or functionally inactivated due to the effects of radiation. The evidence suggests that the highly differentiated cells of the acini and large ducts of mature glands can replace themselves except when the respective pools of available cells are greatly diminished via apoptosis or necrosis owing to severely stressful events. Under the latter circumstances, relatively undifferentiated cells in the intercalated ducts proliferate and redifferentiate as may be required to replenish the depleted pools. It is likely that some, if not many, acinar cells may de-differentiate into intercalated duct-like cells and thus add to the pool of progenitor cells in such situations. If the stress is heavy doses of radiation, however, the result is not only the death of acinar cells, but also a marked decline in functional differentiation and proliferative capacity of all of the surviving cells, including those with progenitor capability. Restoration of gland function, therefore, seems to require increasing the secretory capacity of the surviving cells, or replacing the acinar cells and their progenitors either in the existing gland remnants or with artificial glands.